Advances in Optical Fiber Technology Fundamental Optical Phenomena and Applications - Yasin, Moh; Arof, Hamzah; Wadi Harun, Sulaiman (IntechOpen, 2015)
This book is a compilation of works presenting recent developments and practical applications in optical fiber technology. It contains 13 chapters from various institutions that represent global research in various topics such as scattering, dispersion, polarization interference, fuse phenomena and optical manipulation, optical fiber laser and sensor applications, passive optical network (PON) and plastic optical fiber (POF) technology. It provides the reader with a broad overview and sampling of the innovative research on optical fiber technologies.